2012
DOI: 10.1080/0361073x.2012.726045
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Motor Imagery: Working Memory as a Mediator

Abstract: The main findings indicated that motor imagery ability (generation, visual and kinesthetic imagery ability, controllability, and temporal organization) were better in young adults compared with older adults 70 years and older, but not in older adults 60 to 69 years of age. The analysis of the mediational effect of working memory on age differences in the motor imagery measures showed that the inclusion of working memory increased the amount of explained variance in the MIQ (ΔR (2) = .03), in the CMI test (ΔR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 49 publications
4
38
3
3
Order By: Relevance
“…Changes in MI ability among older adults could, therefore, be caused by an age-related decline in working memory capacity (Jenkins et al, 1999). A recent study examined the meditational effect of working memory capacity in addition to age and explained variance in the MIQ (ΔR² = 0.03), CMI (ΔR² = 0.15), and mental chronometry (ΔR² = 0.16; Schott, 2012). This meditational role of working memory suggests that age related deterioration of MI ability should be interpreted with caution.…”
Section: Motor Imagery Among Older Adultsmentioning
confidence: 98%
“…Changes in MI ability among older adults could, therefore, be caused by an age-related decline in working memory capacity (Jenkins et al, 1999). A recent study examined the meditational effect of working memory capacity in addition to age and explained variance in the MIQ (ΔR² = 0.03), CMI (ΔR² = 0.15), and mental chronometry (ΔR² = 0.16; Schott, 2012). This meditational role of working memory suggests that age related deterioration of MI ability should be interpreted with caution.…”
Section: Motor Imagery Among Older Adultsmentioning
confidence: 98%
“…In fact, screening for cognitive problems and MI ability should be mandatory given the role of working memory in MI and documented working memory problems with aging and stroke (Malouin et al, 2004b, 2010, 2012; Schott, 2012). Both reduced working memory and poor attention skills can make the teaching of MI more difficult (Braun et al, 2010, 2012).…”
Section: Factors Influencing MI Training Outcomesmentioning
confidence: 99%
“…However, the results obtained by Holland and Hill (2010) suggest a link exists between experimental chronometric walking performance and risks taken by older individuals, at least the male participants, when crossing a road. The fact that only females were recruited in the present experiment is thus another limitation, despite that gender differences in walking time estimation have not been reported previously (Holland and Hill, 2010;Schott, 2012).…”
Section: Study Limitationsmentioning
confidence: 55%
“…On real roads approximately 7 m wide, free of incoming traffic, Zivotofsky et al (2012) also observed that able-bodied persons mostly in their 70 s underestimated their crossing duration, whereas younger controls were accurate. Smaller age-related effects were reported by Schott and Munzert (2007) and Schott (2012) who implemented an imagined crossing task that was performed with eyes closed, across distances ranging from 7 m to respectively 25 m or 40 m. The difference between actual and imagined crossing durations was small in participants under 70, regardless of the distance involved. Shorter estimates were provided by older participants, especially those aged 80, but for distances greater than usual road distances (more than 7 m).…”
Section: Introductionmentioning
confidence: 62%